Development, implementation and evaluation of a distance course about wound treatment (Revista Latino-Americana de Enfermagem, 2006)
This research aimed to design, implement and evaluate a distance learning course (DLC), using the Internet, in a virtual environment named TelEduc. Thirty-eight nurses were invited, 28 of whom registered and 17 concluded the course. The specialists and the students evaluated the course and diagnostic (pre-test), process and final (post-test) evaluations were made. Specialists in distance learning and wounds considered the course as adequate but recommended minor adjustments. Most of the students showed a positive opinion about the course. A comparison between pre- and post-test results showed that students scored better on the post-test (p